Scoring the efficiency of portuguese wine exports: an analysis recurring to Stochastic Frontier Models - Mourão, Paulo (2016)
Portuguese wine is recognized as an important source of economic revenues for Portugal. However, revenues from this product declined in most foreign markets in the decade from 2001-2011. In this paper, we will develop an original attempt to identify the most important determinants of the value of Portuguese wine exports and the efficiency levels for each destination country. Our results revealed that the value of Portuguese wine exports has a positive relationship with the size of the government in each destination country, the rural population of the destination country, and real GDP per capita, among other variables. The efficiency of wine exports increased because of the level of inflation and Foreign Direct Investment per capita in the destination economies. We also found that the most efficient destinations are those where Portuguese is the native language, and two of the less efficient cases are Poland and the United States of America, which are cases that deserve special attention from Portuguese exporters and foreign policies.